An Ordinary Differential Equation Model for Simulating Local-pH Change at Electrochemical Interfaces - Mukouyama, Yoshiharu; Nakanishi, Shuji (Frontiers in Energy Research, 2020)
The local pH value at an electrochemical interface (pHs) inevitably changes during redox reactions involving the transfer of H+ or OH− ions. It is important to quantitatively estimate pHs during polarization, as this parameter has a significant impact on the activity and selectivity of electrochemical reactions. Numerical simulation is an effective means of estimating pHs because it is not subject to experimental constraints. As demonstrated in a number of studies, pHs can be estimated by solving partial differential equations that describe diffusion process. In the present work, we propose a method to consider the process by using ordinary differential equations (ODEs), which can significantly reduce the computational resources required for estimating pHs values. In the ODE-based model, the description of the diffusion process was achieved by considering the reaction plane in the diffusion layer over which the H+ and OH− concentrations are balanced while assuming that the concentration profiles in the layer are in a steady state. The resulting model successfully reproduces experimental voltammograms characterized by local pH changes in association with the hydrogen evolution and hydrogen peroxide reduction reactions.